A photographic atlas for the anatomy and physiology laboratory - Van De Graaff, Kent M.; Crawley, John L. (Englewood, Colo. : Morton Pub. Co., 1996)
This full-colour atlas is designed for all students taking either separate or integrated courses in physiology and/or anatomy. The atlas can accompany or augment any human anatomy, human physiology or combined textbook, and should be of particular use in a laboratory situation.
Body organization; cells; histology; integumentary system; skeletal system -- axial portion; skeletal system -- appendicular portion; articulations; muscular systems; nervous sytem; endocrine system; sensory organs; circulatory system; lymphatic system; respiratory system; digestive system; urinary system; reproductive system; developmental biology; cat dissections; foetal pig dissections.
Includes index.
Keywords: Human anatomy